Sub‐Decadal Volcanic Tsunamis Due To Submarine Trapdoor Faulting at Sumisu Caldera in the Izu–Bonin Arc. Issue 9 (12th September 2022) - Sandanbata, Osamu; Watada, Shingo; Satake, Kenji; Kanamori, Hiroo; Rivera, Luis; Zhan, Zhongwen
Abstract: The main cause of tsunamis is large subduction zone earthquakes with seismic magnitudes M w > 7, but submarine volcanic processes can also generate tsunamis. At the submarine Sumisu caldera in the Izu–Bonin arc, moderate‐sized earthquakes with M w < 6 occur almost once a decade and cause meter‐scale tsunamis. The source mechanism of the volcanic earthquakes is poorly understood. Here we use tsunami and seismic data from the recent 2015 event to show that abrupt uplift of the submarine caldera, with a large brittle rupture of the ring fault system due to overpressure in its magma reservoir, caused the earthquake and tsunami. This submarine trapdoor faulting mechanism can efficiently generate tsunamis due to large vertical seafloor displacements, but it inefficiently radiates long‐period seismic waves. Similar seismic radiation patterns and tsunami waveforms due to repeated earthquakes indicate that continuous magma supply into the caldera induces quasi‐regular trapdoor faulting. This mechanism of tsunami generation by submarine trapdoor faulting underscores the need to monitor submarine calderas for robust assessment of tsunami hazards. Plain Language Summary: Tsunamis are mainly caused by large submarine earthquakes, but submarine volcanic processes can also trigger tsunamis. Disproportionately large tsunami waves have been generated every decade by moderate‐sized volcanic earthquakes at a submarine volcano with a caldera structure, called Sumisu caldera, in the Izu–Bonin arc, south of Japan. Despite the moderate earthquake size, the maximum wave heights of the tsunamis were about a meter, and their source mechanism has been controversial. In this study, we used tsunami and seismic data from a recent earthquake to show that the submarine caldera abruptly uplifts due to brittle rupture of its intra‐caldera fault system driven by overpressure of magma accumulating in its underlying magma reservoir and generates large tsunamis almost once a decade. The atypical source mechanism for tsunami generation suggests that it is important to monitor active submarine calderas for assessing tsunami hazards. Key Points: Large tsunamis are generated by moderate‐sized volcanic earthquakes at a submarine caldera Tsunami and seismic data indicate that abrupt uplift of the submarine caldera by trapdoor faulting causes large tsunamis Continuous magma supply into the submarine caldera induces submarine trapdoor faulting on a decadal timescale